2014
DOI: 10.1158/1078-0432.ccr-13-0987
|View full text |Cite|
|
Sign up to set email alerts
|

The Nedd8-Activating Enzyme Inhibitor MLN4924 Thwarts Microenvironment-Driven NF-κB Activation and Induces Apoptosis in Chronic Lymphocytic Leukemia B Cells

Abstract: Background Stromal-mediated signaling enhances NFκB pathway activity in chronic lymphocytic leukemia B-cells (CLL), leading to cell survival and chemoresistance. Ubiquitination of IκBα may partially account for constitutive activation of NFκB. MLN4924 is an investigational agent that inhibits the Nedd8-activating enzyme, thereby neutralizing Cullin-RING ubiquitin ligases and preventing degradation of their substrates. Experimental Design We conducted a pre-clinical assessment of MLN4924 in CLL. Primary CLL c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
125
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(139 citation statements)
references
References 51 publications
13
125
1
Order By: Relevance
“…9,36,37 As indicated above, p53 is not critical for MLN4924-induced Noxa upregulation, as this upregulation was seen in p53 null (HL-60) as well as p53 wild-type cells (ML-1; Figures 3a and c). NF-κB does not appear to have a critical role because, consistent with previous reports, 10,38 NF-κB levels decreased upon MLN4924 treatment and levels of the NF-κB inhibitor (I-κB) increased (Supplementary Figure S2c). Levels of ATF4, another transcription factor implicated in Noxa upregulation, 39 also did not increase (Supplementary Figure S1c), consistent with the observation that MLN4924-induced Noxa upregulation and apoptosis in these AML lines occurs without evidence of elevated ROS or ER stress (Supplementary Figures S1c, d and S2a, b).…”
Section: Mln4924-induced Noxa Upregulation Triggers Apoptosissupporting
confidence: 87%
See 1 more Smart Citation
“…9,36,37 As indicated above, p53 is not critical for MLN4924-induced Noxa upregulation, as this upregulation was seen in p53 null (HL-60) as well as p53 wild-type cells (ML-1; Figures 3a and c). NF-κB does not appear to have a critical role because, consistent with previous reports, 10,38 NF-κB levels decreased upon MLN4924 treatment and levels of the NF-κB inhibitor (I-κB) increased (Supplementary Figure S2c). Levels of ATF4, another transcription factor implicated in Noxa upregulation, 39 also did not increase (Supplementary Figure S1c), consistent with the observation that MLN4924-induced Noxa upregulation and apoptosis in these AML lines occurs without evidence of elevated ROS or ER stress (Supplementary Figures S1c, d and S2a, b).…”
Section: Mln4924-induced Noxa Upregulation Triggers Apoptosissupporting
confidence: 87%
“…These results complement and extend prior work showing that c-Myc, which is generally considered a contributor to proliferation, can contribute to apoptosis, 44,45 particularly under unfavorable growth conditions such as those resulting from environmental alterations or pharmacological manipulation. [18][19][20]36 Collectively, these studies are consistent with the pathway shown in Figure 6, which is different from the cytotoxic mechanism reported in solid tumor cells, 1,33 chronic lymphocytic leukemia, 38 lymphoma, 10 or myeloma, 12 and support the notion that the mechanism of MLN4924-induced cell death downstream of NAE inhibition will vary from cell type to cell type. 1 Importantly, the increases in c-Myc protein, Noxa mRNA and Noxa protein observed in AML cell lines were also observed in AML samples exposed to MLN4924 ex vivo, pointing to a pharmacodynamic marker of NAE inhibition (Noxa upregulation) and possible mechanisms of MLN4924 resistance (diminished c-Myc or Noxa upregulation) that could be investigated in future trials of MLN4924 in AML.…”
Section: Discussionsupporting
confidence: 75%
“…This significant apoptotic response was attributed to the induction of c-FLIP degradation, which the authors showed to be independent of NEDD8 inhibition (67). Furthermore, it is now abundantly clear that hundereds of cellular proteins are regulated through neddylation, and consistently, pevonedistat inhibits several signal transduction pathways, including the NFkB, AKT, and the mTOR signaling pathways, in addition to cullin-signaling (28,29,(63)(64)(65)(66). Thus, pevonedistat may exhibit differential toxicities in HNSCC cells and tumors depending on the genetic backgrounds of the cells or tumors as well as on the concentrations employed.…”
Section: Discussionmentioning
confidence: 99%
“…Pevonedistat inhibits all cullin-based E3 ligases and additionally exhibits cullin-independent activity (28,29,(63)(64)(65)(66)(67). However, the results described above suggest that the radiosensitizing activity of pevonedistat is due to its ability to induce rereplication, which can be enhanced by IR.…”
Section: Induction Of Rereplication Via Cdt2 Depletion or Cdt1 Activamentioning
confidence: 98%
“…MLN4924 targets the NEDD8-activating enzyme, thereby preventing the neddylation (activation) of cullin-RING proteins. This prevents ubiquitination by SCF complexes, promoting apoptosis and autophagy in targeted cells (56,57). We tested MLN4924 for efficacy in rescuing ⌬F508-CFTR-mediated Cl Ϫ transport in CFBE cells at six different doses ranging from 1 nM to 100 M. Unfortunately, MLN4924 was toxic to epithelial cells and was only tolerated at doses that did not inhibit neddylation.…”
Section: Distinct Complexes Degrade ⌬F508-cftr December 2 2016 • Volmentioning
confidence: 99%